A Biallelic Gene Polymorphism of CYP11B2 Predicts Increased Aldosterone to Renin Ratio in Selected Hypertensive Patients - Nicod, Jérôme; Bruhin, David; Auer, Lucas; Vogt, Bruno; Frey, Felix J.; Ferrari, Paolo (The journal of clinical endocrinology and metabolism, 2003)
Altered control of aldosterone synthase (CYP11B2) gene expression may modulate aldosterone secretion, as suggested by a raised aldosterone to renin ratio (ARR) in some patients with essential hypertension.We compared the frequency of two linked CYP11B2 polymorphisms, one in the steroidogenic factor-1 (SF-1) binding site and the other an intronic conversion (Int2) in relation to ARR in 141 hypertensive patients. Patients were divided into groups with either normal or high supine ARR using a cut-off threshold of 145 pmol/liter per ng/liter. Supine ARR was normal in 104 patients and raised in 37 patients. The two polymorphisms were in strong linkage disequilibrium (χ2 = 123.8; P < 0.0001). The SF-1 T and Int2 C alleles were more prevalent among patients with high ARR (46% and 43%, respectively) than with normal ARR (22% and 17%; P < 0.01 and P < 0.005, respectively). Odds ratios for raised ARR in subjects with a homozygous SF-1 T and Int2 C haplotype were 6.1 (95% confidence interval, 1.6–22.5; P < 0.005) when compared with the contrasting haplotype. Linear modeling of individual postural changes in renin and aldosterone showed a maximal achievable aldosterone increase of 110 pmol/liter with no mutated haplotype and 500 pmol/liter with two mutated haplotypes. These findings support the view of a molecular basis regulating aldosterone production.